2006
DOI: 10.1007/s00418-006-0171-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of age-dependent expression of aggrecan and ADAMTSs in mandibular condylar cartilage, tibial growth plate, and articular cartilage in rats

Abstract: A disintegrin and metalloproteinase with thrombospondin motif (adamalysin-thrombospondins, ADAMTS) degrades aggrecan, one of the major extracellular matrix (ECM) components in cartilage. Mandibular condylar cartilage differs from primary cartilage, such as articular and growth plate cartilage, in its metabolism of ECM, proliferation, and differentiation. Mandibular condylar cartilage acts as both articular and growth plate cartilage in the growing period, while it remains as articular cartilage after growth. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
3
25
0
3
Order By: Relevance
“…ADAMTS1 and 5 thus showed the highest expression levels during a phase when MSCs did not synthesise ACAN. This is in line with the detection of ADAMTS1 expression in the resting and proliferative zone of the growth plate of rats (Mitani et al, 2006). The function of these aggrecanases during early phases of differentiation remains unclear and is intriguing, especially for ADAMTS1 which showed high expression levels, comparable to those in normal cartilage.…”
Section: Aggrecanases In Chondrogenesis Of Mscssupporting
confidence: 66%
“…ADAMTS1 and 5 thus showed the highest expression levels during a phase when MSCs did not synthesise ACAN. This is in line with the detection of ADAMTS1 expression in the resting and proliferative zone of the growth plate of rats (Mitani et al, 2006). The function of these aggrecanases during early phases of differentiation remains unclear and is intriguing, especially for ADAMTS1 which showed high expression levels, comparable to those in normal cartilage.…”
Section: Aggrecanases In Chondrogenesis Of Mscssupporting
confidence: 66%
“…Their aggrecanase activity is known to responsible for aggrecan degradation in joint inflammatory diseases (Nagase et al, 2003;Kevorkian et al, 2004;Demircan et al, 2005;Bondeson et al, 2008). It has also been reported that expressions of ADAMTS1, 4, and 5 were found in the growth plate of the rat tibia (Jungers et al, 2005;Mitani et al, 2006), although there were no morphological difference between wild type and targeted mutant mice against ADAMTS1, 4, or 5 genes (Glasson et al, 2004;Little et al, 2005;Stanton et al, 2005). In the present study, we demonstrated for the first time that ADAMTS9 is expressed at mRNA and protein levels in the mouse tibia growth plate.…”
Section: Discussionmentioning
confidence: 99%
“…Mitani et al (2006) investigated the expression patterns of ADAMTS1, 4, and 5 in the rat mandibular condylar cartilage, and articular and growth plate cartilage and concluded that ADAMTS5 might mainly contribute to the extracellular matrix metabolism in the growth plate and condylar cartilage during growth. In contrast ADAMTS1 and ADAMTS4 may be involved in the extracellular matrix turnover in the articular cartilage in relation to ADAMTSs specific substrates such as aggrecan, brevican, and versican.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandibular condylar cartilage acts as both articular and growth plate cartilage in the growth period, while it remains as articular cartilage after growth. Mitani et al (2006) have shown now that functional and ECM diVerences between condylar and primary cartilages are associated with diVerences in gene expression patterns and levels of aggrecan and adamalysinthrombospondins (ADAMTS)-1, -4, and -5 during growth and aging. Heparan sulfate proteoglycans (HSPGs) are another abundant component of the pericellular matrix of both developing and mature cartilage and their distribution during murine cartilage growth plate development was investigated by Gomes et al (2006).…”
Section: Skeletal Muscle Cartilage and Ecmmentioning
confidence: 99%